Community preparedness for disaster risk reduction from Islamic perspectives in promoting dam disaster management - Sabri Muda, Rahsidi; Tukiman, Izawati; Ahmad Sarkawi, Azila; Md Amin, Mohamad Faiq; Mohd Khidzir, Ainul Bahiah (Zes Rokman Resources, 2019)
Dams are constructed for many reasons to supply human needs in daily life such as water supply, power generation and etc. However, dams could impose risks to the public and the situation could be disastrous if the dam break occurred, and catastrophic flood is direct impact to downstream area. The impact of dam break is unpredictable, thus requires better understanding and preparedness to avoid fatalities and minimize damages and losses. The purpose of this paper is to discover an effective approaches to encourage public involvement in the reduction process of growing disaster risk in developing countries which inline with Islamic teaching. The relationship between religious beliefs and natural disaster will be the focus discussed in this paper. Content analysis of journals, books, national and international guidelines on disaster risk management are used to discover various opinions, actions and religious relationship that support for a better disaster risk management. The Islamic perspectives highlighted on human believe, culture and behavior, safety and vitality in order to clear existing misunderstandings and it shows that the issues of environment protection, risk management, safety and human life in terms of Islamic religious demonstrate of God's love for mankind.